Triggering Factors for Organism' Evolution - Do Sepachai; Yuuyen Pathompul (Journal La Lifesci, 2021)
The purpose of the article is to know the trigerring factor for arganism’ Evolution. Evolution is defined as the change in the heritable features of a population of organisms from one generation to the next, or from one generation to the next. Evolution, according to the contemporary conception, is characterized by changes in the attributes of living organisms through time, with these changes being guided by the process of natural selection